Birthplace diversity and team performance - Enzo Brox; Tommy Krieger (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
We present a simple model to illustrate how birthplace diversity may affect team performance. The model assumes that birthplace diversity increases the stock of available knowledge due to skill complementarities and decreases effciency due to communication barriers. The consequence of these two opposing effects is a humpshaped relationship between birthplace diversity and team performance. To verify this prediction, we exploit self-collected data on the first division of German male soccer. Our data set covers 7,028 matches and includes information about 3,266 players coming from 98 countries. We propose two different instrumental variable approaches to identify the effect of birthplace diversity on team performance. Our findings suggest that an intermediate level of birthplace diversity maximizes team performance.
Keywords: F23; F66; J01; J24; M14; M54; 330; birthplace diversity; firm performance; globalization; high-skilled migration; international migration; productivity; soccer; team composition; team performance